(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Voice commerce - is a technology based on artificial intelligence which helps to do shopping just with costumer’s voice and a smart device like a mobile phone or smart speaker. Conversational AI simplifies everyday tasks. For retailers, that means consumers can use their voice to find the item they need, make an order, pay for it, track it, and leave feedback when it arrives. Later, they can use purchase history to reorder their products. And it works both for online and physical shops. Voice activated shopping has become very popular and well liked even before 2022.